Bedforms of Thwaites Glacier, West Antarctica: Character and Origin - Alley, R.B.; Holschuh, N.; MacAyea, D.R.; Parizek, B.R.; Zoet, L.; Riverman, K.; Muto, A.; Christianson, K.; Clyne, E.; Anandakrishnan, S.; Stevens, N.T. (Penn State Data Commons, 2020)
Bedforms of Thwaites Glacier, West Antarctica both record and affect ice flow. Thwaites Glacier flows across the tectonic fabric of the West Antarctic rift system with its bedrock highs and sedimentary basins. Swath radar and seismic surveys of the glacier bed have revealed soft-sediment flutes 100 m or more high extending 15 km or more across basins downglacier from bedrock highs, and ending at prominent hard-bedded moats on stoss sides of the next topographic highs. We use simple models to show that ice flow against topography generates high pressure between ice and till upglacier along the bed over a distance that scales with the topography. This high pressure would exclude ice-contact water there and thus increase ice-till coupling and till flux there, removing till to allow bedrock erosion and create moats. Till carried across highlands would then be deposited in lee-side positions, remaining soft on top to approach steady-state by matching till-deformational fluxes from upglacier of the topography, and prograding downglacier over time. The bedforms of the part of Thwaites surveyed here are prominent because ice flow has persisted over a long time on this geological setting, not because ice flow is anomalous. Bedform development likely has caused evolution of ice flow over time.